ADDITIONAL RECORDS AND PHYLOGENETIC RELATIONSHIPS OF Fejervarya moodiei (Taylor, 1920) (ANURA: DICROGLOSSIDAE) FROM VIETNAM - Van Chung, Hoang; The Cuong, Pham; Quang Truong, Nguyen (Journal of Forestry Science and Technology, 2022)
Kurniwan et al. (2010) specified the distribution of F. cancrivora to the south of the Isthmus of Kra and a large area in the North of the Isthmus of Kra, including Vietnam, is the distribution range of F. moodiei, but the samples analyzed in that study did not include samples collected from Vietnam. Based on the results of morphological and genetic analyses on two mitochondrial gene fragments (16S and Cytb) of populations of Fejervarya moodiei and F. cacrivora, this study confirmed that the Northern Crab-eating Frog F. moodiei distributed in Vietnam. In addition, we recorded the distribution of this species in the mangrove areas of the Thai Binh and Thua Thien Hue provinces as well as Hai Phong city. Although the Fejervarya moodiei populations are widely distributed from the Philippines to Bangladesh, the genetic differences in the 16S and Cytb genes are insignificant (from 0.2 to 1.5% on 16S gene). Morphological data of specimens of F. moodiei from Vietnam and China are also provided.